Optimizing winter sportswear design and service priorities in China: a multi-model assessment - Yang, Kun; Liu, Wenduo; Song, Zhengxue (Frontiers in Sports and Active Living, 2025)
BackgroundPeople who maintain regular outdoor exercise in winter face many environmental and climatic challenges. Therefore, it is crucial to clearly prioritize the attributes of consumer demand for winter sportswear.PurposeThis study aims to identify the ranking of attributes that Chinese consumers of outdoor sports products value in their demand for winter sportswear.Participants and methodsThis study collected data from sports enthusiasts in China's cold winter regions through an online questionnaire (the final effective data set contains 483). The scale collected attribute data on consumer needs for sportswear functions, pricing, service, design, and brand. Each survey includes consumer evaluations of the importance and performance of demand attributes. Demographic surveys include information on age, purchasing experience, and recent requirements. Finally, the results are statistically analyzed using t-test, IPA, Borich needs, and LF.ResultsTop Priority includes color, ergonomics, logo and accuracy (shown as priority in IPA, Need and FL results). Second Priority includes logistics, packaging, return & exchange policy (shown as priority in Need and FL results). Third Priority includes technical cost, fabrics cost and quality control cost (only shown as priority in IPA result).ConclusionThe top three attributes that consumers care about most in the Chinese winter sportswear market are, in order of priority: design, service and pricing.